A Comparative Study on Phytochemical And Biological Activities of two Grewia Species - Khanal, Dharma Prasad; Raut, Bechan; Kafle, Manoj (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background Medicinal plants are currently in considerable significance view due to their special attributes as a large source of therapeutic phytochemicals that may lead to the development of novel drugs. Herbs are staging a comeback and herbal ‘renaissance’ is happening all over the globe. The herbal products today symbolize safety in contrast to the synthetics that are regarded as unsafe to human and environment. It has been estimated that in developed countries such as United States, plant drugs constitute as much as 25% of the total drugs, while in fast developing countries such as China and India, the contribution is as much as 80%. Thus, the economic importance of medicinal plants is much more to countries such as Nepal than to rest of the world. Inventorisation of herbal drugs used in traditional and modern medicines for a country like Nepal, appears to be a stupendous task, where a number of well established indigenous or traditional systems, including Ayurveda, Unani, Siddha, Homoeopathy, Tibetan, Amchi, Yoga and Naturopathy are practiced along with modern medicine for the management of total health care system. Method Classic techniques for the solvent extraction of active constituents from medicinal plant matrices are based on the choice of solvent coupled with the use of heat. Soxhlet extraction is a general and well-established technique, which surpasses in performance other conventional extraction techniques. : In this method, finely ground sample of Grewia species were placed in a porous bag or “thimble” made from a strong filter paper or cellulose, which is place, is in thimble chamber of the Soxhlet apparatus. Extraction solvents was heated in the bottom flask, vaporizes into the sample thimble, condenses in the condenser and drip back. When the liquid content reaches the siphon arm, the liquid contents emptied into the bottom flask again and the process is continued. The resultant extracts were used for qualitative phytochemical analysis by color reactions, antibacterial effects by disc diffusion method and Human RBC membrane stabilization method was used to test the anti-inflammatory potential of the phytoconstituents. Findings Two species Grewia asiatica and Grewia optiva (family: Tiliaceae) from genus Grewia were studied for their phytochemical and biological properties. The result showed that the extractive value of Grewia optiva was found to be greater (2.56 % in hexane and 7.17 % in methanol) than Grewia asiatica (n-hexane 2.24% and methanol 5.04%) respectively. The test for the phytoconstituents for both species showed the presence of glycosides, steroids, tannins, flavonoids, terpenoids and saponins. No any extract of both species at dose of (0.25mg, 0.5mg and 1mg per cup) possessed a zone of inhibition against tested bacterial strains. The potency of n-hexane extract and methanol extract of both species for Human RBC membrane stabilization test were compared with standard Diclofenac potassium. HRBC stabilization and resulted a good membrane stabilization of n-hexane extract of Grewia asiatica (40.89%, 73.57%, 78.23%, 80.07%, 80.91% and 51.95%) at (50 μg/ml, 100μg/ml, 200μg/ml, 400μg/ml, 600μg/ml and 800μg/ml) than methanol extract of both species. The result of the both species possessed similar phytochemicals and showed some membrane stabilization property which supports the traditional use. Conclusion Alkaloids were absent in the Grewia species extracts. The tested extracts have no any antibacterial effects against the tested bacterial stamps. The human RBC membrane stabilization tests were compared with standard Diclofenac potassium showed the good membrane stabilization of n-hexane extract of Grewia asiatica indicating the potent anti-inflammatory effect. Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.53-60